KANAK BARAJININ OTURMA VE SIZMA DEĞERLERİNİN NÜMERİK ANALİZ SONUÇLARIYLA KARŞILAŞTIRILMASI - MEMİŞOĞLU, VEYSEL (Fırat Üniveristesi, 2019)
Baraj; su toplama, sulama, içmesuyu ve elektrik üretmek amacı ile bir vadinin iki yakası arasına değişik tip ve malzemeden inşa edilen su yapısıdır. Bu çalışmada, Sivas ili Şarkışla ilçesinde yapımı tamamlanmış Kanak Barajının sonlu elemanlar modeli oluşturularak şev stabilitesi, oturmaları, sızma miktarı ve sızma hatlarının durumları ile iki farklı deprem altında lineer dinamik analizleri sonlu elemanlar yöntemini kullanan bilgisayar programı yardımıyla elde edilmiştir. Analizlerden elde edilen oturma ve sızma miktarı değerleri Devlet Su İşleri 19. Bölge Müdürlüğünden temin edilen ve Kanak Barajında kullanılan ölçüm aletlerinin sonuçlarıyla karşılaştırılmıştır. Sızma analizi için baraj rezervuarının maksimum su seviyesinde olduğu kabul edilmiştir. Dinamik analizler için 1992 Erzincan ve 2003 Bingöl depreminin ivme kayıtları kullanılmıştır.

A dam is a water structure, which is constructed between the two sides of a valley in varios types and by various materials, in order to provide water collection, irrigation, drinking water and electricity production. In this study, the finite element model of Kanak Dam, which construction is completed in Şarkışla district of the city of Sivas, was formed and analyses of slope stability, settlements, seepage amount and seepage lines along with linear dynamic analyses under two different earthquakes were conducted by the help of a software using the finite element method. The values of settlement and seepage obtained from the analyses were compared with the results of the measurement instruments used in the Kanak Dam, which were obtained from the 19th Regional Directorate of State Hydraulic Work. The dam reservoir was regarded to be at the maximum water level for seepage analysis. For dynamic analyses, the acceleration records of 1992 Erzincan and 2003 Bingöl earthquake were used.
The comparison of the seepage and settlement values of Kanak dam with the numerical analysis results
Keywords: İnşaat Mühendisliği